Analisis Rasio Profitabilitas dan Rasio Aktivitas sebagai Dasar Penilaian Kinerja Keuangan pada PT. Indofood - Ompon Lastiur Sianipar; Eka Pratiwi Septiana Parapat (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
The purpose of this research was to determine the financial performance at PT. Indofood Sukses Makmur Tbk from 2012 to 2014. The data analysis method used is the documentation and the data obtained from www.indofood.co.id. The ratio is a tool used in this study to compare the amount of data one with another amount of data used to assess the financial position in a given period. The ratio used of which is the liquidity ratio as represented by the current ratio and the quick ratio, the solvency ratio is represented by the debt ratio and total debt to equity ratio and profitability ratio represented by return on assets and return on equity. The results in the study from 2012 to 2013 from liquidity ratio seen from the current ratio and quick ratio decreased. The increase occurred in 2013 to 2014 due to the increase in current assets so that liabilities can be met. Thus PT. Indofood Sukses Makmur Tbk included in either category. Seen from the solvency ratio of the debt ratio and Total Debt to Equity Ratio insufficient capital companies underwriting debt by creditors so that PT. Indofood Sukses Makmur Tbk is said to be better than the year 2012-2014. From the ratio of profitability seen in return on assets and return on equity declined in 2012 to the year 2013. The increase occurred in 2013 to 2014 due to the efficiency in using assets to make a profit so that the state of the PT. Indofood Sukses Makmur tbk termasuk in both categories